Implementation of P5 work titles in increasing the sense of unity and unity of students and teachers at SDN Warungdowo I - Laili, Innayatul; Damayanti, Ayu Maya; Azhar Ramadhani, Reviandy (Institute of Computer Science (IOCS), 2024)
The implementation of the P5 Work Title in increasing the sense of unity and oneness between students and teachers at SDN Warungdowo I is the main focus of this research. The aim of the research is to examine the process of carrying out degree work, analyze its influence on increasing the sense of unity and oneness, and provide practical recommendations to increase the effectiveness of this program. The research method used is qualitative, by observing the process of implementing work degrees and analyzing its impact. The results of the research show that harmonization of cultural diversity, instilling a sense of unity and oneness, as well as promoting diversity through the P5 Karya degree are the main keys in improving social ties at SDN Warungdowo I. Teachers act as facilitators who guide students in understanding and implementing the values ??of Pancasila. The traditional game approach is an effective method for increasing a sense of unity, where students are invited to interact, collaborate and support each other. The conclusion of this research emphasizes that the traditional game approach has proven effective in increasing the level of unity and integrity at SDN Warungdowo I. This shows the importance of implementing activities based on local culture and values ??in improving the quality of education. and strengthen social ties in the school environment.